2018
DOI: 10.1002/aenm.201801913
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Charge Transfer State Enables Very LowVOCLosses in SWCNT:Fullerene Solar Cells

Abstract: cells, [1][2][3][4] but also other types based on small molecule:fullerene [5,6] blends as well as solar cells incorporating singlewalled carbon nanotubes (SWCNTs) [7][8][9][10][11][12][13][14] were investigated with increased efforts. All of these new concepts have been introduced to tackle several drawbacks and outstanding issues related to polymer:fullerene solar cells. [15] Concepts such as small molecule:fullerene active layers aim to use simple, well-defined molecules instead of polymers, which always ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…The effective band gap ( E gap ) is determined by the crossing point between absorption spectra of films and EL spectra of relevant devices (Figure S13) . As shown in Table , in contrast to the Rh‐OH:PC 71 BM blend with a E gap of 1.83 eV, the E gap of Rh‐PC 71 BM is larger with a value of 1.91 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective band gap ( E gap ) is determined by the crossing point between absorption spectra of films and EL spectra of relevant devices (Figure S13) . As shown in Table , in contrast to the Rh‐OH:PC 71 BM blend with a E gap of 1.83 eV, the E gap of Rh‐PC 71 BM is larger with a value of 1.91 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Thee ffective band gap (E gap )i sd etermined by the crossing point between absorption spectra of films and EL spectra of relevant devices ( Figure S13). [44] As shown in Table 1, in contrast to the Rh-OH:PC 71 BM blend with a E gap of 1.83 eV,t he E gap of Rh-PC 71 BM is larger with av alue of 1.91 eV.Notably,the E loss (0.93 eV) of the Rh-PC 71 BM device is lower than that of the Rh-OH:PC 71 BM device which has a E loss E CT of 0.95 eV.Here,byapplying the FTPS signals and Equation (2), we further fitted and calculated the E CT values of 1.55 eV for Rh-PC 71 BM film and 1.45 eV for Rh-OH:PC 71 BM blend, respectively.I ti sf ound that the energy loss for the formation of the CT state (DE 1 )i nt he Rh-PC 71 BM device is 0.36 eV.H owever,t he Rh-OH:PC 71 BM binary device shows a DE 1 of 0.38 eV.The results suggest that the Rh-PC 71 BM device possess efficient exciton dissociation to overcome the exciton binding energy (E b )o ft he D/A moieties of the pristine Rh-PC 71 BM film. In addition, the E loss due to recombination, which consists of radiative recombination (DE 2 )and nonradiative recombination (DE 3 ), exhibits the same value (0.57 eV) in Rh-PC 71 BM and Rh-OH:PC 71 BM devices.N evertheless,t he DE 2 value (0.22 eV) of the Rh-PC 71 BM device,w hich is dependent on the additional radiative recombination below the E gap ,i sh igher than that of the Rh-OH:PC 71 BM binary device (DE 2 = 0.10 eV), indicating that the Rh-OH:PC 71 BM BHJ blend is better for overcoming the Coulomb binding energy of the CT state.The final term of the nonradiative recombination loss (DE 3 )c an be geminate or non-geminate and includes recombination through structural defects or energetic traps,triplet states,and Auger recombination, etc.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Organic molecular blends based on fullerene acceptors (FAs), have been in the focus of intensive research efforts in the organic solar cell community, due to their reliable performance in the solar energy conversion [1,2]. Despite the recent advent of non-fullerene acceptor systems [3,4] with power conversion efficiencies reaching 18% [5], FA-based blends remain important model systems to study key electronic and optoelectronic processes and limiting factors of organic photovoltaic devices [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…6,[17][18][19][20] In OPV devices, s-SWCNT films have shown high values for both internal and external quantum efficiency (IQE and EQE), [21][22][23] and it has also been suggested that CT states are absent, leading to low nonradiative open-circuit voltage (V oc,nonrad ) loss. 24 The photodynamics of exciton dissociation and charge recombination processes at heterojunctions between s-SWCNTs and various electron acceptors such as fullerenes, 6,17,25,26 perylene diimides (PDIs), 19 and two-dimensional (2D) molybdenum disulfide (MoS 2 ) monolayers 20 have been explored, and the charge separation processes therein occur rapidly, in the range of 120 fs-1.6 ps, with charge recombination times often exceeding 1 ms. The ultrafast charge separation and long-lived charge separated states from s-SWCNT-based heterojunctions are often attributed to a high degree of charge carrier delocalization in the s-SWCNTs phase, resulting in the fast extraction of charge carriers from the donor-acceptor interface after exciton dissociation.…”
Section: Introductionmentioning
confidence: 99%